Modified Tricomi Problem for a Nonlinear System of Second Order Equations of Mixed Type (Journal of Partial Differential Equations, 1999)
In this paper a nonliuear system of second order equations of mixed type is considered. The existence of H¹ strong solution for the modified Tricomi problem is proved by the energy integral method and the Leray-Schauder's fixed point principle.
Keywords: Nonlinear system of second order equations of mixed type; modified Tricomi problem: energy integral method: Leray-Schauder's fixed point principle